Medication Adherence and Glycemic Control among Patients With Type 2 Diabetes Enrolled in a Chronic Disease Management Program in Primary Care Settings - Asep Sukohar; Reimma Emily Rachman; Nistita Abighail; Septia Eva Lusina; Muhammad Akmal Ghani (International Journal of Health and Pharmaceutical (IJHP), 2026)
Medication adherence plays a crucial role in achieving optimal glycemic control in patients with type 2 diabetes mellitus. However, poor glycemic control remains common despite the availability of antidiabetic therapy through the Chronic Disease Management Program (Prolanis), and evidence regarding this association among program participants is still limited. This study aimed to analyze the association between antidiabetic medication adherence and glycemic control based on HbA1c levels in patients with type 2 diabetes mellitus enrolled in Prolanis. An analytical observational study with a cross-sectional design was conducted among 118 Prolanis participants at primary health care facilities in Lampung Province, Indonesia, in 2025 using consecutive sampling. A total of 118 respondents were included in the final analysis, with a mean age of 54.09 ± 10.66 years. Medication adherence was assessed using the Morisky Medication Adherence Scale-8, while glycemic control was evaluated based on HbA1c categories. Data were analyzed using the Chi-square test with a significance level of p < 0.05. The results showed that most respondents had moderate medication adherence (38.1%) and poor glycemic control (50.8%). A significant association was found between medication adherence and glycemic control (p = 0.037; Cramér's V = 0.208), indicating a small-to-moderate effect size. These findings highlight the need to strengthen adherence-focused interventions, including patient education, routine monitoring, and continuous support, as part of Prolanis implementation to improve long-term glycemic outcomes in primary care settings.